UNDERSTANDING CUSTOMER BEHAVIOUR OF PURCHASING LUXURY PRODUCT THROUGH THE LENS OF COMPLEMENTERY THEORY - Hasnun Anip Bustaman; Ismail Ishak; Maznah Abdullah; Nik Rozhan Nik Ismail (International Journal of Accounting, Finance and Business, 2024)
This research examines the complex interaction of cultural, economic, and social elements that influence consumer behavior towards luxury items in the Malaysian online market. The cultural meaning of luxury products is strongly influenced by society ideals that prioritize status and prestige, leading to a widespread desire for these things as indicators of social position. The economic delves into increasing in disposable income among Malaysian consumers associated with rising inclination towards luxury products. Furthermore, the study investigates the significant influence of brand perception on purchase intentions, clarifying the connection between luxury brands and characteristics such as exclusivity, quality, and social standing. The phenomena are fully analyzed by gathering information through cross sectional survey study. Significantly, the assessment of the worth and excellence of high-end goods in relation to their cost emerged as a crucial factor for buyers. In addition, this study emphasizes the important impact of peer influence and society norms in changing people's intents to make purchases. Recommendations and societal validation are identified as crucial factors that strongly affect the decision-making process. Marketing methods, namely those implemented via social media platforms and influencer endorsements, have a substantial role in molding customer attitudes. The key is consumers' exposure to luxury markets worldwide. This exposure plays a role in shaping the changing patterns of luxury consumption in the country. This study enhances comprehension of the intricate forces that influence the desire to buy luxury goods in Malaysia, providing useful knowledge for marketers and firms seeking to connect with the Malaysian consumer market.